## Tìm x : a, 7 – 3 x ( x + 1 ) =1 b, 12 : ( x + 5 ) +4 = 6 c, 5 x ( 2 nhân x – 3 ) + 1 = 16 d, 7 + 4 : (

Question

Tìm x :
a, 7 – 3 x ( x + 1 ) =1 b, 12 : ( x + 5 ) +4 = 6
c, 5 x ( 2 nhân x – 3 ) + 1 = 16 d, 7 + 4 : ( 5 – 2 nhân x ) = 11

in progress 0
1 năm 2021-09-07T08:39:23+00:00 2 Answers 7 views 0

## Answers ( )

1. a, 7 – 3 × ( x + 1 ) =1

3×(x+1)=7-1

3×(x+1)=6

x+1=6:3

x+1=2

x=2-1

x=1

$\text{Vậy x=1}$

b, 12 : ( x + 5 ) +4 = 6

12:(x+5)=6-4

12:(x+5)=2

x+5=12:2

x+5=6

x=6-5

x=1

$\text{Vậy x=1}$

c, 5 × ( 2 × x – 3 ) + 1 = 16

5×(2x-3)=16-1

5×(2x-3)=15

2x-3=15:5

2x-3=3

2x=3+3

2x=6

x=6:2

x=3

$\text{Vậy x=3}$

d, 7 + 4 : ( 5 – 2 × x ) = 11

4:(5-2x)=11-7

4:(5-2x)=4

5-2x=4:4

5-2x=1

2x=5-1

2x=4

x=4:2

x=2

$\text{Vậy x=2}$

2. a, 7 – 3 . ( x + 1 ) =1

3 . ( x + 1 ) = 7 – 1

3 . ( x + 1 ) = 6

x + 1    = 6 : 3

x + 1    = 2

x           = 3

b, 12 : ( x + 5 ) +4 = 6

12 : ( x + 5 )      = 6 – 4

12 : ( x + 5 )      = 2

x + 5        = 12 : 2

x + 5        = 6

x               = 1

c, 5 x ( 2 . x – 3 ) + 1 = 16

5 x ( 2 . x – 3 )       = 16 – 1

5 x ( 2 . x – 3 )       = 15

2 . x – 3        = 15 : 5

2 . x – 3        = 3

2 . x             = 3 + 3

2 . x             = 6

x             = 3

d, 7 + 4 : ( 5 – 2 . x ) = 11

4 : ( 5 – 2 . x )  = 11 – 7

4 : ( 5 – 2 . x )  = 4

5 – 2 . x   =  4 : 4

5 – 2 . x    = 1

2 .x     = 5 – 1

2 .x     = 4

x      = 4 : 2

x      = 2